The 1996 subaqueous eruption at Academii Nauk volcano (Kamchatka) and its effects on Karymsky lake - Fazlullin S.M.; Ushakov S.V.; Shuvalov R.A.; Aoki M.; Nikolaeva A.G.; Lupikina E.G. (My University, 2000)
A subaqueous eruption in Karymsky lake in the Academii Nauk caldera dramatically changed its water column structure, water chemistry and biological system in less than 24 h, sending major floodwaves down the discharging river and eruption plumes with ash and gases high into the atmosphere. Prior to the eruption, the lake had a pH of about 7, was dominated by bicarbonate, and well stocked with fish, but turned in early 1996 into a stratified, initially steaming waterbody, dominated by sulfate with high Na and K levels, and devoid of fish. Blockage of the outlet led to rising waterlevels, followed by dam breakage and catastrophic water discharge. The total energy input during the eruption is estimated at about 1016 J. The stable isotope composition of the lake water remained dominated by the meteoric meltwaters after the eruption.
Keywords: 38.37.25 Вулканология; Академии Наук; Карымский